QUANTUM AND QUASI-CLASSICAL CALCULATIONS ON THE OH+CO-]CO2+H REACTION - Clary, D; Schatz, G (1993)
Scattering calculations on the OH+CO→CO2+H reaction are reported using both quantum and quasiclassical methods. The rotating bond approximation is used in the quantum calculations. This method explicitly treats the OH vibration and CO rotation in the reactants and the bending vibration and a local CO stretch in the CO2 product. Analogous quasiclassical trajectory computations are also reported. A potential energy surface obtained as a fit to ab initio data is used. The quantum reaction probabilities are dominated by sharp resonances corresponding to vibrationally excited states of the HOCO complex formed in the reaction. The quantum and quasiclassical lifetimes of these resonances compare quite well with measurements made by Wittig et al. Calculations of differential cross sections, rate coefficients, and CO2 vibrational product distributions are also compared with experimental data. The comparisons of quantum and quasiclassical calculations for models that treat explicitly different numbers of degrees of freedom provide detailed insight into the dynamics of the OH+CO reaction. © 1993 American Institute of Physics.